Gestión de la demanda y oferta de agua de riego en el ámbito de la irrigación sisa – san martín - Pizarro Baldera, José Del Carmen (2010)
Currently in the field of Irrigation Sisa, located in the department of San Martin, there is the problem of inadequate availability of irrigation water to supply the demand of crops developed there. In this regard, the present research work aims to identify and analyze the causes that originate it, in order to make a proposed solution most appropriate. For that purpose has been necessary to use the materials formed by water, the irrigated area and crops that are planted there, the current status of irrigation infrastructure, customers or applicants of irrigation water, and the officials responsible for system administration or irrigation water suppliers. The methodology has been inductive and comparative, since existing information about the problem, collection of field information through direct interviews of users, the card and the current crop water demand of the system have been reviewed and analyzed. The result has been obtained that for an area of 14,366.93 ha of rice crop; water demand is from MMC 207.57, while the supply of water in the river Sisa is 861.84 MMC. After the water balance was done, the excess is 654.27 MMC, which shows that the problem is not water supply, but it is located within the irrigation system, that is to say the component includes irrigation water demand, which depends from several factors including: the efficiency of irrigation, crop type, water infrastructure, users.